Answer: here is your steps Simplifying
8x + -37 = 5x + 17
Reorder the terms:
-37 + 8x = 5x + 17
Reorder the terms:
-37 + 8x = 17 + 5x
Solving
-37 + 8x = 17 + 5x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-5x' to each side of the equation.
-37 + 8x + -5x = 17 + 5x + -5x
Combine like terms: 8x + -5x = 3x
-37 + 3x = 17 + 5x + -5x
Combine like terms: 5x + -5x = 0
-37 + 3x = 17 + 0
-37 + 3x = 17
Add '37' to each side of the equation.
-37 + 37 + 3x = 17 + 37
Combine like terms: -37 + 37 = 0
0 + 3x = 17 + 37
3x = 17 + 37
Combine like terms: 17 + 37 = 54
3x = 54
Divide each side by '3'.
x = 18
Simplifying
x = 18
Step-by-step explanation: